(untitled) (International Current Pharmaceutical Journal, 2014)
Perindopril erbumine is a tert-butylamine salt of perindopril used in the treatment of stable coronary artery disease and hypertension. The present study was aimed to evaluate the anaphylactic reaction as an adverse event for perindopril erbumine tablets. Electronic extraction of data from the safety database for this report includes all cases of anaphylactic reaction where perindopril was a primary or co-suspect drug. The study result have shown that there were overall 205 case reports for perindopril in the database, of which 200 cases were assessed as (potentially) perindopril and 05 were assessed as non-perindopril product. From the 200 case reports, 141 were serious and 59 were non-serious. Out of the 141 serious cases, 137 cases were medically confirmed while remaining 04 cases were consumer reports. Of the total 205 case reports there were five cases wherein the patient experienced anaphylactic reaction. The study concludes that three out of five cases entered in the drug safety database suggestive of a possible association between perindopril and anaphylactic reaction. DOI: http://dx.doi.org/10.3329/icpj.v3i4.18265 International Current Pharmaceutical Journal, March 2014, 3(4): 254-258